Model for measuring the diffusion of process innovations within online content providers (2013)
Since the emergence of the Internet, commercial sectors have included this technology in their business processes. This inclusion has led to the digitalization of their processes and their business models itself. The most modified business model by the digitalization process was the content provider. This model is considered tacitly innovative and a source of economic growth. For this reason, countries like Colombia have established policies to promote and strength the digital content sector by implementing process innovations oriented to the generation of this type of content. However, the formulated policies evidenced the need to find mechanisms for measuring the process of appropriation of process innovations. The objective of this paper is to show the formulation of the doctoral project that pretends to solve the problem of measuring appropriation, as well as to shows the conceptual advances reached in the first stage of development.